Raça, cultura e pertencimento: a emergência da noção de diáspora africana - Cauê Gomes Flor (Ciências Sociais Unisinos)
In the last twenty years, we have seen substantial transformations both in the place that is attributed to the peoples, cultures and traditions of African origin in the formation of Brazilian society, and in the way national identity is approached in the debates and discussions that are dedicated to the investigation of relations in the contemporary world. These transformations take a path that reflects a new look at the presence of these peoples and cultures, often informed and influenced by a concept that has gained prominence in the discussions in both the academic world and militancy: the African diaspora. However, the model or perspective of the African diaspora that is being articulated in these investigations and discourses is rarely explicit. Outside Brazil, the notion of the diaspora, and more specifically of the African diaspora, is not recent. Since the end of the 19th century it was present in the United States, having an important role as a locus of belonging, contributing to the building of solidarities and political agendas of the black American social movements. In addition, the notion of the African diaspora was essential for the construction, institutionalization and postulation of theoretical-methodological paradigms for what is now (recently) termed African-American Studies. In this sense, this work aims to elaborate a brief genealogy of the notion of African diaspora. Through mapping the way African-American intellectuals worked with categories such as “race,” “culture,” “affiliation,” and “belonging” in the late 19th century, we present the emergence conditions of the concept.